Mechanism of action of lenalidomide in hematological malignancies - Kotla, Venumadhav (BioMed Central, 2009)
Immunomodulatory drugs lenalidomide and pomalidomide are synthetic compounds derived by modifying the chemical structure of thalidomide to improve its potency and reduce its side effects. Lenalidomide is a 4-amino-glutamyl analogue of thalidomide that lacks the neurologic side effects of sedation and neuropathy and has emerged as a drug with activity against various hematological and solid malignancies. It is approved by FDA for clinical use in myelodysplastic syndromes with deletion of chromosome 5q and multiple myeloma. Lenalidomide has been shown to be an immunomodulator, affecting both cellular and humoral limbs of the immune system. It has also been shown to have anti-angiogenic properties. Newer studies demonstrate its effects on signal transduction that can partly explain its selective efficacy in subsets of MDS. Even though the exact molecular targets of lenalidomide are not well known, its activity across a spectrum of neoplastic conditions highlights the possibility of multiple target sites of action.